IFRS adoption and audit delay: the case of the large French listed companies - Lobna Fathi Loukil (STIE Malangkucecwara, 2023)
Abstract Listed French companies in European regulated markets were required to present their consolidated accounts using the international financial reporting standards (IFRS) from 1 January 2005. This study investigates the impact of this adoption on audit delay, which is the number of days from a company’s fiscal year-end to the date of its auditor’s report. The sample used in this paper is a panel of 69 French firms over a period of 6 years (2002-2007). Data was gathered from the SBF 250 index. The fixed effects regression results show that the transition to IFRS is associated with a significant increase in audit timeliness. This significant rise in audit delay occurred only in 2005, but was not found during the post-IFRS period. This paper proved the complexity of the IFRS and thus auditors required more hours in performing their audit engagement. The contribution of this study is to investigate an audit report in a developed capital market (listed French firms) by taking advantage of access to proprietary data on audit delay and audit fees. Keywords: IFRS, Audit delay, French firms, complexity.